Esbozo de teoría contramayoritaria : consideraciones de la "countermajoritarian difficulty" - Rivera León, Mauro Arturo (Teoría y Realidad Constitucional, 2011)
The present article deals with the countermajoritarian difficulty but not from a substantial perspective but with its inner characteristics. I try to offer considerations about the violated majority and a useful distinction to the countermajoritarian decisions attending the emitting organ and the passive subject. A brief analysis about the implications of the democratic conceptions and pluralism to the countermajoritarian discussion is provided. I argue that the present categories of the countermajoritarian argument are insufficient to comprehend the problem, giving as a result the necessity of further considerations about the type of majority and majoritarian conditions violated. El presente artículo aborda el estudio del argumento contramayoritario pero no desde una perspectiva sustancial sino en sus características intrínsecas. Se pretende aportar a la discusión consideraciones sobre el tipo de mayoría vulnerada y una distinción útil a la clasificación de las decisiones contramayoritarias atendiendo al órgano emisor de la decisión y al sujeto pasivo en la misma. De igual manera se provee un breve análisis de las implicaciones de las concepciones democráticas y del pluralismo a la discusión contramayoritaria. Se sostiene que las categorías del estudio del argumento contramayoritario resultan insuficientes que para la comprensión del problema son necesarias mayores consideraciones en torno a las mayorías y condiciones mayoritarias vulneradas.